Physicochemical Modulation by Tapioca Starch in Oyster Mushroom (Pleurotus ostreatus) Powder - Sofia Maru; Erni Setijawaty; Ignasius Radix AP Jati (JFCN: Journal of Food, Culinary, and Nutrition, 2026)
Oyster mushroom (Pleurotus ostreatus) is a nutritious and affordable food ingredient; however, its high moisture content results in a short shelf life. This study aimed to evaluate the effect of tapioca concentration on the physicochemical properties of oyster mushroom powder. The experiment was arranged in a single-factor randomized block design with six levels of tapioca concentration (2.5, 5.0, 7.5, 10.0, 12.5, and 15.0%) and four replications. Observed parameters included moisture content, water activity (aw), color characteristics (lightness, chroma, and hue), protein content, and crude fiber content. Data were analyzed using analysis of variance (ANOVA) at a 5% significance level, followed by Duncan’s Multiple Range Test when significant differences were observed. The results showed that oyster mushroom powder had moisture content of 2.65–5.84%, aw of 0.145–0.506, lightness of 64.26–74.70, chroma of 10.42–18.90, hue of 76.50–83.74, protein content of 7.93–13.00%, and crude fiber content of 4.95–9.57%. Increasing tapioca concentration significantly reduced moisture content, aw, protein content, and crude fiber content of the powder.